Schools and Staffing Survey 1990-91 Data File User's Manual. Volume I: Survey Documentation - Gruber, Kerry J.; Rohr, Carol L.; Fondelier, Sharon E.; Pinkerton Computer Consultants, Inc., Baileys Crossroads, VA.; Bureau of the Census (DOC), Suitland, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1994)
This volume documents the data collection of the 1990-91 Schools and Staffing Survey (SASS). People wishing to determine whether their research needs can be served by SASS data will find a description of the survey's contents and objectives in the Overview. This volume contains the following chapters: (1) "Overview"; (2) "Changes in SASS Design and Content from 1998 to 1991"; (3) "Preparation for the 1991 SASS"; (4) "Sample Design and Implementation"; (5) "Data Collection"; (6) "Response Rates"; (7) "Edit Procedures"; (8) "Imputation Procedures"; (9) "Weighting"; (10) "Variance Estimation"; (11) "Reinterview Program"; (12) "Reviewing the Quality of SASS Data"; (13) "Cautions Concerning the Measurement of Change Estimates Using 1987-88 and 1990-91 SASS"; (14) "Confidentiality Protection Measures"; (15) "Created Variables"; and (16) "User Notes." Seven appendixes contain supplemental information about the survey. (Contains 153 tables and 21 figures.) (SLD)
Availability: National Center for Education Statistics, Office of Educational Research and Improvement, 555 New Jersey Avenue, NW, Washington, DC 20208-5651.
Sponsoring Agency: National Center for Education Statistics (ED), Washington, DC.
ERIC Note: For volumes II and III, see ED 435 733-734.
Researchers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Coding; Data Analysis; Elementary Secondary Education; National Surveys; Research Methodology; Response Rates (Questionnaires); Sample Size; Sampling; School Personnel; School Statistics; Teachers; User Needs (Information); Schools and Staffing Survey (NCES); Data Files; Guides, Non-Classroom.